Accelerating Digital Adoption: A Case Study on Capacity Building for SMES and Cooperatives in Bekasi Regency - Genoveva, Genoveva; Manurung, Siska Purnama; Rahmiati, Filda (Abdimas Galuh, 2025)
By 2024, the number of MSMEs in Indonesia will reach 66 million and contribute 99.6% to employment in Indonesia. However, only 17% of MSMEs are familiar with digital technology. In order to realize the achievement of Level Up SMEs and Cooperatives, the Office of Cooperatives and SMEs carries out various coaching in their respective cities and districts. On July 23-25, 2024, the Bekasi Regency SME and Cooperative office held a workshop to improve the digital capabilities of SMEs and Cooperatives. The number of participants was 150 registered SMEs and cooperatives, where participants were divided into 50 people for each batch. The material was provided by two lecturers of the Management study program, President University. The delivery of the material was carried out practically, given the different educational backgrounds and types of businesses. The material includes how to create appropriate marketing content, such as short videos on TikTok, including using other social media, namely Instagram and Facebook and online marketplaces. Participants were guided step by step using their laptops or mobile phones, so that they could understand the material well. This workshop provided benefits to the participants, as well as provided an opportunity for lecturers from President University to carry out community service in accordance with their expertise, and realize the work plan of the Bekasi Regency SME and Cooperative Office, namely leveling up for SMEs and Cooperatives.